Faktor-Faktor Penyerahan Perwalian Nikah kepada Penghulu di KUA Kec. Maritengngae Kab. Sidrap - Nur Thaharah Buhana; Zaenab Zaenab; Aswar Aswar (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2023)
AbstractThis research was conducted with the aim of knowing (1) the process of handing over marriage guardianship to the head of the KUA Kec. Maritengngae; (2) what are the factors that cause the handover of marriage guardianship to the head of the KUA Kec. Maritengngae. This research is a field research using an empirical juridical approach with data collection techniques through observation, interviews and documentation. Based on the results of the research in the field, it shows that: 1. In the process of the marriage contract for those who submit marriage guardianship, previously the power of attorney was transferred to the represented party. Before the pledge is made, the Head of KUA/Penghulu reminds the guardian that it is better/afdal if it is the guardian himself who marries. If the guardian is at the place of the marriage contract then the handover of guardianship is direct but if the guardian is not at the place of the marriage contract then the handover of guardianship is in writing/taukil bil kitabah, i.e. the submission is through the KUA where the guardian is located to be known by the Head of the KUA, then the letter is sent / brought directly to the KUA's place for his son who will do the wedding, but at the KUA Kec. Maritengngae are more likely to hand over marriage guardianship directly. 2. The cause of the submission of marriage guardianship to the head of the KUA Kec. Maritengngae is caused by 4 factors, namely, habit/custom factors, psychological factors, educational factors, and health factors.